Ilse Nolting-Hauff, Vision, Satire und Pointe in Quevedos "Sueños". Wilhelm Fink Verlag, München, 1968; 240 pp. (Poetica, Beiheft, 3). - Barrientos, Juan José (El Colegio de México, 1971)
Se reseñó el libro: Vision, Satire und Pointe in Quevedos "Sueños".